Attention deficit and reading comprehension of Andean texts in children who study at moderate altitude - Mamani, Grecia (2020)
The problem of attention deficit and the level of reading comprehension in children is a problem that teachers must pay attention to; since it is present in the personal, social and community areas and cognitive, emotional and interactive behaviors of children. Therefore, the objective of the study was to know the attention deficit and the reading comprehension of an Andean text in children who are at 3800 meters above sea level when they study it in conditions of low temperatures. In the study, it was observed that 13.8% of children have ADHD; however, 10.3% of this population is at the beginning of the reading comprehension process, this being significant. ADHD and meager reading comprehension is a real problem that teachers must know and face in order to apply appropriate strategies and techniques, for the development of children it is essential the importance that they must give to this disorder and its corresponding monitoring since this is of vitally important to be able to act in a relevant and effective way so that children's learning.